Ab initio Calculations of the Electronic-Energy Structure and Optical Properties of Lanthanum and Neodymium Pyrozirconates - A. A. Lavrentyev; B. V. Gabrelian; Vu Van Tuan; K. F. Kalmykova (Advanced Engineering Research, 2025)
Introduction. Compounds with lanthanum and neodymium (La2Zr2O7 and Nd2Zr2O7) have low thermal conductivity, high permittivity and melting point, stability and resistance to defects. They can be used for thermal insulation of metal components in turbines and air engines. Also, these compounds are widely studied from the point of view of the development of materials science, particularly, for the improvement of laser technology and optics. However, the physical properties of La2Zr2O7 and Nd2Zr2O7 have not been sufficiently studied experimentally. This gap is intended to be filled by the presented study. The research objective includes model calculations of the electronic structure and optical properties of La2Zr2O7 and Nd2Zr2O7.Materials and Methods. Based on model calculations within the framework of the density functional theory, the electron-energy structure of pyrozirconates La2Zr2O7 and Nd2Zr2O7, containing Zr and having the crystal structure of pyrochlore was investigated. The parameters of the crystal lattice of La2Zr2O7 taken from the literature were used in the calculations. Due to the lack of experimental data, the parameters for Nd2Zr2O7 were calculated by minimizing the forces acting on the atoms of the compound. A combined exchange-correlation potential was used, taking into account the strong interactions of d- and f-electrons of La and Nd atoms with a correction in the form of a modified Becke-Johnson meta-potential. Wien2K software package was used for the calculations.Results. The densities of electron states of all atoms of the studied compounds were obtained. The calculated densities of valence electron states of the compounds were compared to the experimental X-ray photoelectron spectra. At zero energy, the optical characteristics of La2Zr2O7 and Nd2Zr2O7 were calculated. Firstly, it was the permittivity: for La2Zr2O7 — 8.4334, for Nd2Zr2O7 — 8.501; secondly, refraction: for La2Zr2O7 — 2.904, for Nd2Zr2O7 — 2.916; thirdly, reflection: for La2Zr2O7 — 23.786%, for Nd2Zr2O7 — 23.935%. High optical absorption coefficient (˃10⁵ cm⁻¹) was recorded in the ranges: from 5 to 14 eV, from 14 to 28 eV, and from 28 to 40 eV. Peak extinction values were in the ranges from 5 to 13 eV, from 14 to 28 eV, and from 28 to 40 eV. La2Zr2O7 and Nd2Zr2O7 crystals could absorb photons in a wide energy range (4–10 eV).Discussion and Conclusion. The study supplemented the concept of the properties of La2Zr2O7 and Nd2Zr2O7 with new experimental data. The densities of electron states and optical spectra of La2Zr2O7 and Nd2Zr2O7 compounds were calculated. This made it possible to explain features of the experimental X-ray photoelectron spectra of the compounds. In the approximation of the modified Becke-Johnson potential, the values ​​of the widths of the forbidden bands of the compounds corresponding to the experimental ones were obtained. The research is fundamental and can open up prospects for creating more efficient, reliable and functional materials, laser and optical devices.